More than one way to evolve a weed: parallel evolution of US weedy rice through independent genetic mechanisms. Issue 13 (19th June 2015) - Qi, Xinshuai; Liu, Yan; Vigueira, Cynthia C.; Young, Nelson D.; Caicedo, Ana L.; Jia, Yulin; Gealy, David R.; Olsen, Kenneth M.
Abstract Many different crop species were selected for a common suite of 'domestication traits', which facilitates their use for studies of parallel evolution. Within domesticated rice (Oryza sativa), there has also been independent evolution of weedy strains from different cultivated varieties. This makes it possible to examine the genetic basis of parallel weed evolution and the extent to which this process occurs through shared genetic mechanisms. We performed comparative QTL mapping of weediness traits using two recombinant inbred line populations derived from crosses between an indica crop variety and representatives of each of the two independently evolved weed strains found in US rice fields, strawhull (S) and blackhull awned (B). Genotyping‐by‐sequencing provided dense marker coverage for linkage map construction (average marker interval <0.25 cM), with 6016 and 13 730 SNPs mapped in F5 lines of the S and B populations, respectively. For some weediness traits (awn length, hull pigmentation and pericarp pigmentation), QTL mapping and sequencing of underlying candidate genes confirmed that trait variation was largely attributable to individual loci. However, for more complex quantitative traits (including heading date, panicle length and seed shattering), we found multiple QTL, with little evidence of shared genetic bases between the S and B populations or across previous studies of weedy rice. Candidate gene sequencing revealed causal genetic bases for 8 of 27 total mapped QTL. Together these findings suggest that despite the genetic bottleneck that occurred during rice domestication, there is ample genetic variation in this crop to allow agricultural weed evolution through multiple genetic mechanisms.